PENGARUH KONSENTRASI GARAM TERHADAP FERMENTASI CINCALOK UDANG REBON (Acetes erythraeus) SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PADA PEMBELAJARAN BIOTEKNOLOGI SMA - Wulan Sari; Imam Mahadi; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to determine the effect of salt concentration on fermentation cincalok rebon shrimp (Acetes erythraeus) and the design of Student Worksheet (LKPD) of senior high school grade XII biotechnology materials in January-March 2019. This research carried out in two stages; they are the experimental stage: the effect of salt concentration on fermentation cincalok rebon shrimp (Acetes erythraeus) and the designing stage of the LKPD: the analysis of the potential development of senior high school grade XII biotechnology material for teaching. The research used the experimental method by conducting experiments in the Laboratory of the Faculty of Fisheries and Marine Sciences Riau University, Pekanbaru. Sampling was carried out with a completely randomized design (CRD) consisting of 5 treatments and 3 replications. The parameters in this study were water content, protein content and pH. Based on the results of Analysis of variance (Anova) at the level of 5%, the administration of salt concentration showed a significant effect on fermentation cincalok rebon shrimp (Acetes erythraeus).The provision of salt with a concentration of 20% gave the best increase in the quality of fermentation cincalok rebon shrimp (Acetes erythraeus) and based on the analysis of the research results, it can be used as a draft students worksheet (LKPD) of senior high school grade XII biotechnology materials.Key Words: Fermentation Cincalok Rebon Shrimp, LKPD Design, Salt